RESPONSIVITAS PELAYANAN PUBLIK DALAM MENANGANI KELUHAN PELANGGAN DI PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN NGANJUK - Fega Herdini; Agus Widiyarta (Jurnal Penelitian Administrasi Publik, 2020)
Water Supply Company (PDAM) on Nganjuk Regency is a company engaged in services namely the provision of clean water needs. In its operation, the Nganjuk Regency PDAM is still faced with various problems. This can be seen from the large number of customer complaints related to the provision of clean water needs, looking at problems that occur in the provision of clean water services in Nganjuk Regency, it is important to see how responsive public services are in handling customer complaints so that the services provided are in line with what the community expects as a recipient of services so that better service can be realized. This type of research is qualitative research. The research location is in the Nganjuk District Water Supply Company (PDAM). The focus of this study is based on the size of responsiveness according to Zeithaml cited Hardiyansyah (2018: 63), namely: 1. Responding to each customer, 2. Speed ​​of service, 3. Accuracy of service, 4. Accuracy of officers, 5 Accuracy of service time, 6. Officers respond to all customer. Data collection techniques by observation, interview, and documentation. The results obtained based on 6 indicators used are, there are still some shortcomings such as the lack of response of officers in responding to customer complaints by telephone, there are still obstacles experienced by officers such as the number of technical officers available in the field, the presence of customers is difficult to adjust to the officers, conditions in the field which causes slow handling, and the officer does not provide information about the certainty of time and delay in handling. The conclusion obtained in this study is the responsiveness of services in PDAM Nganjuk Regency is good, but in its implementation there are still some shortcomings.Keywords : Responsiveness, Public services, customer complaints